Analisis Pendapatan dan Risiko Usahatani Tembakau di Subak Gede Sukawati, Gianyar - DEWI, NI LUH PRIMA KEMALA; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Analysis of Income and Risk of Tobacco Farming in Subak Gede Sukawati, Gianyar.  Indonesia is a fertile country with a tropical climate, which makes Indonesia have great potential to produce commodities in the agricultural sector. Gianyar Regency also uses its agricultural land, apart from planting rice and growing secondary crops, farmers also plant plantation crops, one of which is community tobacco plants with an area of 215 ha. Subak Gede Sukawati, in accordance with the existing awig-awig, must be planted alternately for one year. The planting period for tobacco plants planted in Subak Gede Sukawati, which is a community tobacco plant, only lasts once a year, starting from February-May of the same year, starting from cultivating the land to harvesting with a plant age of between 105-121 days. The population is all farmers who were farming tobacco at the time the research was conducted. The sample was determined as 30 farmers using accidental sampling. Farming income is the difference between the farming income obtained and the total farming expenditure. The farming business being carried out is considered profitable if the total income is greater than the total farming expenditure, conversely if the total income is less than the total farming expenditure then the farming business is said to be making a loss. Risk and uncertainty appear in the variations in results obtained by farmers. Where the results obtained are sometimes good or high or conversely the results obtained are low. Farmers cannot predict the outcome, but farmers can only accept it as it happens. Likewise, prices, costs, pests and diseases, as well as profits are caused by uncertainty, so that income or farming profits are variable.